Design and Testing of a Shock Absorber Disassembly Installation Tool: Perancangan dan Pengujian Alat Pemasangan untuk Pembongkaran Peredam Kejut - Akhmad Akhirudin; Mulyadi; Rachmat Firdaus; Iswanto (Indonesian Journal of Innovation Studies, 2025)
General Background: Shock absorbers are critical components in heavy vehicle suspension systems, functioning to reduce vibration and absorb kinetic energy generated by uneven road surfaces. Specific Background: Maintenance procedures involving shock absorber disassembly and installation commonly require substantial force, extended working time, and present safety risks when performed using conventional manual methods. Knowledge Gap: Existing approaches for servicing shock absorbers lack a dedicated tool that combines operational simplicity, time efficiency, and safer handling during both removal and installation processes. Aims: This study aimed to design, manufacture, and evaluate a tracker-based tool for shock absorber disassembly and installation. Results: The proposed tool was designed using SolidWorks Professional 2018 and fabricated from AISI 1035 steel through cutting, drilling, and assembly processes. Testing results showed the fastest shock absorber spring removal time of 1 minute 25 seconds with an average of 1 minute 29 seconds, while the fastest installation time was 2 minutes 2 seconds with an average of 2 minutes 6 seconds. Spring analysis produced a constant of 71.42 kg/cm² under a 250 kg load and 20 kg/cm² under a 70 kg load. Novelty: The study presents a multifunctional tracker-based mechanical tool specifically developed to support both disassembly and installation of heavy-vehicle shock absorbers while incorporating structural design and numerical simulation evaluation. Implications: The developed tool provides a practical solution for reducing work duration and supporting safer maintenance operations in shock absorber servicing applications.Highlights: Tracker-based equipment completed spring removal within an average of 89 seconds. Assembly procedures required approximately 126 seconds across repeated trials. Structural evaluation and load calculations confirmed operational suitability for maintenance tasks. Keywords: Shock Absorber; Mechanical Tool Design; Suspension Maintenance; Numerical Simulation; Spring Constant